2018
DOI: 10.1590/1678-992x-2016-0387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transportation stress on quality and sensory profiles of Nile tilapia fillets

Abstract: This study evaluated pre-slaughter stress and its influence on the stress indicators, quality characteristics and sensory characteristics of Nile tilapia fillets. To this end, two experiments were conducted: (1) two transportation times (60 and 240 min), with a density of 200 kg m-3 , were compared to control treatment fish (in which the fish were removed from the net cage and immediately euthanized); and (2) two transportation densities (100 and 400 kg m-3), transported for 180 min, compared with control trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
3
10
1
1
Order By: Relevance
“…In the correlation analysis, the acceptability was more related to the juiciness of the fillets. A previous study has shown that less stressed tilapia produces meat with higher WHC, lower water loss by pressure and higher juiciness [43]. In the present study, the lower acceptance may be related to the changes observed in the instrumental quality (greater tenderness, greater lightness and lower redness).…”
Section: Discussionsupporting
confidence: 51%
“…In the correlation analysis, the acceptability was more related to the juiciness of the fillets. A previous study has shown that less stressed tilapia produces meat with higher WHC, lower water loss by pressure and higher juiciness [43]. In the present study, the lower acceptance may be related to the changes observed in the instrumental quality (greater tenderness, greater lightness and lower redness).…”
Section: Discussionsupporting
confidence: 51%
“…However, WHC evaluation at different times of the day indicated a higher WHC for animals slaughtered in the early evening, and the plasma glucose level of the fish was also lower in this period. Similarly, a previous study reported a direct relationship between a higher level of stress in fish (with higher plasma glucose levels) and lower WHC in fillets of Nile tilapia (Goes et al, 2018). The lower WHC of meat increases the release of exudate and produces drier meat with less nutritional value (Zeola et al, 2007).…”
Section: Discussionmentioning
confidence: 70%
“…Also, although not described for propofol, transport studies have shown a negative and delayed correlation between cortisol and glucose concentrations in blood plasma, with the cortisol peak being reached immediately after the stressful situation while glucose increased over time [ 83 ]. However, recent reports have also suggested a similar trend between cortisol and glucose plasmatic levels in the transport of Nile tilapia [ 84 ]. The increase of glucose at the end of transport could indicate stress caused by propofol.…”
Section: Discussionmentioning
confidence: 76%